2014
DOI: 10.1557/jmr.2014.365
|View full text |Cite
|
Sign up to set email alerts
|

With great structure comes great functionality: Understanding and emulating spider silk

Abstract: The overarching aim of biomimetic approaches to materials synthesis is to mimic simultaneously the structure and function of a natural material, in such a way that these functional properties can be systematically tailored and optimized. In the case of synthetic spider silk fibers, to date functionalities have largely focused on mechanical properties. A rapidly expanding body of literature documents this work, building on the emerging knowledge of structure-function relationships in native spider silks, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 140 publications
(185 reference statements)
0
10
0
Order By: Relevance
“…[ 28 ]. Additionally, great efforts are made to overcome these issues with the intensive research on recombinant spider silk [ 34 , 60 ]. By tuning the structure to suite the physical and environmental demands of an application, mechanical properties could be adapted to the specific requirements.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ]. Additionally, great efforts are made to overcome these issues with the intensive research on recombinant spider silk [ 34 , 60 ]. By tuning the structure to suite the physical and environmental demands of an application, mechanical properties could be adapted to the specific requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Spider silk is an outstanding proteinaceous fibre that outperforms other natural and synthetic fibres in tensile strength analyses. In addition to fibre strength, spider silks can also be tough, lightweight, highly extensible/flexible, biodegradable and stable across a broad temperature range [ 1 ]. Studies have also demonstrated the biocompatibility of spider silk: spider silk can be implanted into living tissue without eliciting an immune response [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a combined investigation of processing, design, structure, and function will substantially advance the field. Focusing on the extrusion of the silk protein solution will be a key for the next generation of engineered fibers, as it could be that the properties of the end product are more sensitive to the processing and extrusion of the dope solution compared to the protein sequence [66].…”
Section: Spider Silk Fibers: a Leap In Materials Tribologymentioning
confidence: 99%